The Faktor Determinan Minat UMKM terhadap Penggunaan Aktual Menggunakan Cloud Accounting - Annisa Suvia; Nayang Helmayunita (Universitas Negeri Padang, 2024)
This study aims to find evidence that the UTAUT (Unified Theory of Acceptance and Use of Technology) model is a conceptual framework for explaining the acceptance and use of cloud accounting as an online accounting service in the city of Padang. The data used in this study are primary data obtained by distributing questionnaires in person and online. This study used purposive sampling with a sample of 340 respondents who had used cloud accounting. The data analysis used in this research is Structural Equation Modeling (SEM). Data analysis techniques using SmartPLS ver.4.0 were processed. This study found evidence that social influences, facilitating conditions and positive influences on behavioral intentions; behavioral intention to actual use has a positive effect, while performance expectations and effort expectations have a negative effect on behavioral intention.